Combined Detection of RUNX3 and EZH2 in Evaluating Efficacy of Neoadjuvant Therapy and Prognostic Value of Middle and Low Locally Advanced Rectal Cancer - Wang, Likun; Wu, Xueliang; Xu, Wengui; Gao, Lei; Wang, Ximo; Li, Tian (Frontiers in Oncology, 2022)
Background: This study sought to evaluate the role of RUNX3 and EZH2 in evaluating clinical efficacy of neoadjuvant therapy and prognosis of locally advanced rectal cancer (LARC). Methods: Forty-five LARC patients admitted to Tianjin Medical University Cancer Institute/Hospital and First Affiliated Hospital of Hebei North University from January 2015 to January 2016 were included in this study, followed by a 60 months-follow-up visit. All patients received neoadjuvant chemoradiotherapy (long range radiotherapy + oral capecitabine) + total mesorecta excision (TME) surgery. Results: Finally, A total of 45 patients with LARC were enrolled in this study. Expression of RUNX3 was high in 10 (22.22%) patients, whereas EZH2 expression was high in 24 (53.33%) patients. Analysis of tumor regression identified 7 cases of TRG grade 0 (PCR), 13 cases of TRG grade 1, 19 cases of TRG grade 2, and 6 cases of TRG grade 3. Furthermore, 24 cases had significant down-staging, and 21 cases showed no significant down-staging as shown by endoscopy and imaging evaluation. Logistic regression analysis showed that high RUNX3 expression, low EZH2 expression, CT stage and CN stage were good predictors of tumor regression response and down-staging. Among the 45 patients, the 5-year DFS was 64.44 (29/45) and the 5-year OS was 77.78% (35/45). The 5-year DFS and 5-year OS of patients with high Runx3 expression were significantly higher compared with those with low Runx3 expression, whereas the 5-year DFS and 5-year OS of patients with high EZH2 expression were significantly lower compared with those with low EZH2 expression (P < 0.05). Univariate survival analysis showed that RUNX3 expression, EZH2 expression, cN, cT, pT and pN were significantly correlated with 5-year DFS and 5-year OS. Multivariate survival analysis showed that EZH2 expression and PN were good predictors of 5-year DFS and 5-year OS, whereas RUNX3 was a good predictor of 5-year DFS but not 5-year OS. Conclusions: Expression of RUNX3 and EZH2 can accurately evaluate treatment efficacy of neoadjuvant chemoradiotherapy and effective predictors of the prognosis of LARC patients. Therefore, RUNX3 and EZH2 has significant clinical implications.